Biliary dilatation in the presence of a periampullary duodenal diverticulum - Lee, J J (Br J Radiol, 2015)
OBJECTIVE: Periampullary diverticulum (PAD) often presents as an incidental CT finding. Its significance and its effect on biliary dilation are unclear. The aim of our study was to determine if the presence of a PAD is associated with abnormal dilation of the common bile duct (CBD). METHODS: Patients with PAD were retrospectively identified from the radiology database from November 2011 to November 2012 and those with known pancreaticobiliary pathology were excluded, except patients with cholelithiasis and prior cholecystectomy. A total of 150 patients with PAD were selected as well as a control group of 150 patients with no PAD. Data with respect to demographics, PAD size and location, ductal diameter, previous cholecystectomy and liver function tests were collected. To compare the groups, the Student's t-test and χ(2) analysis were used where appropriate. RESULTS: The male : female ratio was 1 : 1.2 with a median average of 71 years in the PAD group. There was no statistical difference in the CBD measurement (at the pre-ampulla and pancreatic head, and distal to confluence) between the PAD and control groups (4.8, 6.9 and 6.8 mm for the PAD group; 4.7, 6.8 and 6.4 mm for the control group; p = 0.5, 0.7 and 0.3). Also, no difference was observed in the right and left intrahepatic biliary ducts (2.7, 2.7 mm for the PAD group; 2.5, 2.6 mm for the control group; p = 0.2, 0.6). There was a significantly higher incidence of cholecystectomy history (23% vs 8.7%, p < 0.01) and cholelithiasis (22% vs 11%, p < 0.01) in the PAD group, and no difference in the liver function tests. Subgroup analysis of small vs large PAD (<20 mm, ≥20 mm) did not show a difference in the CBD and intrahepatic biliary duct measurements. When comparing cholecystectomy vs non-cholecystectomy groups, CBD measurements were significantly higher in the cholecystectomy group. CONCLUSION: Our study confirms that PAD on its own does not lead to abnormal CBD dilatation. However, increased incidence of cholelithiasis and cholecystectomy was noted in the presence of PAD. ADVANCES IN KNOWLEDGE: PAD on its own does not cause CBD dilatation.